VISUAL MERCHANDISE'S MARKETING COMMUNICATION AND ITS EFFECT ON CONSUMER PURCHASE BEHAVIOUR IN THE RETAIL SECTOR IN PUNE - Sharma, Preeti; Longani, Kirti Dang (Universitas Muhammadiyah Jakarta, 2023)
Visual merchandising is recognized as a marketing communication tool used by retailers to communicate the store or company's fashion value and quality image to prospective consumers. It involves the presentation of products in a visually appealing way to attract and engage shoppers. The main aim of visual merchandising includes educating consumers, enhancing the store's image, and encouraging multiple sales. This is achieved by displaying apparel and accessories together, which can encourage cross-selling and upselling. A distinctive aspect of this study will be its focus on the unique supermarkets of Pune City. Pune, with its diverse demographic and rapidly evolving retail environment, presents a fertile ground for examining how visual merchandising influences consumer behavior in supermarkets. The city's supermarkets range from local favorites to national chains, each offering a different experience in terms of product variety, pricing, and store design. Understanding these nuances will provide a comprehensive picture of how visual merchandising can be optimized to meet the needs and preferences of Pune's shopper. By incorporating the specific background and characteristics of Pune City Supermarkets into the study, contribute valuable localized insights to the broader discourse on visual merchandising and consumer behavior in the retail sector. The study focuses on Visit Frequency and Time Spent in supermarkets and how much time they spend during each visit. Also, focus on the reasons for the choice of supermarket and Consumer Behaviour in Supermarkets. This may involve factors such as location, pricing, product range, and, the general appearance of the store and available facilities. Emphasis on the general opinions on Supermarket Appearance and buying behavior with reference to Visual Merchandise. This may involve observing whether the placement of products and visual displays affects purchasing decisions. It's essential to conduct this kind of research to understand consumer preferences and behaviours better. Retailers can use this information to tailor their visual merchandising strategies and store layouts to attract and retain customers. Additionally, feedback on the overall shopping experience and reasons for choosing a particular supermarket can inform marketing and business strategies.